When is blockchain worth it? Value and risk drivers of corporate blockchain announcements - Timo Rogalski; Dirk Schiereck (Electronic Markets, 2024)
In the era of emerging technologies, many firms explore the role of blockchain technology and its impact on corporate market value. Past research has shown that companies benefit from executing blockchain projects, but little is known about specific value and risk drivers. Hence, we provide evidence for several conditions under which blockchain provides additional firm market value. Moreover, we test whether blockchain announcements lead to changes in the systematic risk of firms. Theoretically founded on the resource-based view, we utilize the event study methodology, supplemented by a multivariate regression and a firm's beta analysis. We find that stock markets react positively to corporate blockchain news if the announcement is related to a blockchain consortium or partnership, is declared by a tech company, or if the announcement is a follow-up announcement to initial blockchain news. Moreover, our findings show that blockchain announcements do not lead to significant changes in a firm's systematic risk.
Keywords: G14; 620; Blockchain; Market value; Market risk; Event study